Insertion of Ni(0) and Pd(0) precursors into the Si–Si bond of a disilane with two hypercoordinate silicon atoms. Issue 60 (25th June 2020) - Usui, Ryosuke; Sunada, Yusuke
Abstract : The activation of the silicon–silicon bond in disilane Ph2 Si(μ-Pz Me2 )2 SiPh2 (1 ), which possesses two five-coordinate silicon centers, was achieved by a reaction with Pd(CN t Bu)2 or in situ generated Ni(0)–NHC precursors of modest steric demand. Abstract : The activation of the silicon–silicon bond in disilane Ph2 Si(μ-Pz Me2 )2 SiPh2 (1 ), which possesses two five-coordinate silicon centers, was achieved by a reaction with Pd(0) or Ni(0) precursors of modest steric demand to afford a dinuclear Pd complex (2 ) or two types of mononuclear Ni complexes (3 and 4 ), respectively.